The HER2 flip-HER2 amplification of tumor cells in the cerebrospinal fluid of breast cancer patients with leptomeningeal disease: implications for treating the LM tumor with anti-HER2 therapy - Kumthekar, Priya U.; Blouw, Barbara; Corkos, Perry; Nagpal, Seema; Tripathy, Arushi; Piccioni, David; Youssef, Michael (Frontiers in Oncology, 2024)
Introduction CNSide is a platform that detects and characterizes tumor cells in the cerebrospinal fluid (CSF) of patients with leptomeningeal disease (LMD). The platform was validated per College of American Pathologists (CAP) and Clinical Laboratories Improvement Amendment (CLIA) guidelines and run as a commercial Laboratory Developed Test (LDT) at Biocept in San Diego, CA. The platform allows CSF tumor cell (CSF-TC) enumeration and biomarker characterization by fluorescent in situ hybridization (FISH). Methods We performed a multicenter retrospective chart review of HER2 FISH CNSide test results that were commercially ordered on 26 patients by physicians for LMD breast cancer patients between April 2020 and October 2022. Results We show that HER2 is amplified on CSF tumor cells in 62% (16/26) of LMD breast cancer patients. 10/26 (38%) patients had discordant HER2-positivity between the primary tumor tissue and CSF-TC; of these, 35% (9/26) of the patients displayed HER2 amplification on the CSF-TCs, however were categorized as HER2 negative on the primary tumor. Of the 27% (7/26) patients with a HER2 positive primary tumor, one patient showed a HER2 negative LMD tumor. Two patients, 8% (2/26) had a HER2 equivocal primary tumor; of these, one demonstrated a HER2 negative, and one a HER2 positive LMD tumor. Serial analysis (at least 4 longitudinal tests) of HER2 status of the CSF-TC throughout therapy was available for 14 patients and demonstrated that HER2 status of the LMD changed in 29% (4/14) during their treatment course and impacted care decisions. Conclusions Our data suggests that CSF-TC HER2 FISH analysis in LMD breast cancer patients may be discordant to the primary tumor sample and the discovery of HER2 positivity in the CSF may open doors to anti-HER2 targeted therapy options for LMD patients.